Properties of 0-degree domain walls in cubic ferromagnet in transverse magnetic field - Vakhitov, R.M.; Zainullina, A.S.; Ryakhova, O.G. (Functional Materials, 2012)
The paper investigates the influence of an external magnetic field on the structure and properties of a 0° domain wall in an infinite cubic ferromagnet with uniaxial anisotropy induced along the [001] axis. In the case when the field is perpendicular to the plane of spin rotation (transverse fields), its presence results in the magnetization vector leaving the domain wall plane and its rotation relative to the crystallographic axes. Numerical and approximated analytical solutions have been found that correspond to magnetic inhomogeneities with such a structure.